Effect of a pragmatic home-based mobile health exercise intervention after transcatheter aortic valve replacement: a randomized pilot trial. Issue 1 (4th February 2021) - Lindman, Brian R; Gillam, Linda D; Coylewright, Megan; Welt, Frederick G P; Elmariah, Sammy; Smith, Stephanie A; McKeel, David A; Jackson, Natalie; Mukerjee, Kush; Cloud, Harrison; Hanna, Narden; Purpura, Jenelle; et al.
Abstract: Aims: Impaired physical function is common in patients undergoing transcatheter aortic valve replacement (TAVR) and associated with worse outcomes. Participation in centre-based cardiac rehabilitation (CR) after cardiovascular procedures is sub-optimal. We aimed to test a home-based mobile health exercise intervention as an alternative or complementary approach. Methods and results: At five centres, after a run-in period, eligible individuals treated with TAVR were randomized 1:1 at their 1-month post-TAVR visit to an intervention group [activity monitor (AM) with personalized daily step goal and resistance exercises] or a control group for 6 weeks. Among 50 participants, average age was 76 years, 34% were female, average STS score was 2.9 ± 1.8, and 40% had Short Physical Performance Battery (SPPB) ≤9. Daily compliance with wearing the AM and performing exercises averaged 85–90%. In the intention to treat population, there was no evidence that the intervention improved the co-primary endpoints: daily steps +769 (95% CI −244 to +1783); SPPB +0.68 (−0.27 to 1.53); and Kansas City Cardiomyopathy Questionnaire −1.7 (−9.1 to 7.1). The intervention did improve secondary physical activity parameters, including moderate-to-intense daily active minutes ( P < 0.05). In a pre-specified analysis including participants who did not participate in CR ( n = 30), the intervention improved several measures of physical activity: +1730 (100–3360) daily steps; +66 (28–105) daily active minutes; +53 (27–80) moderate-to-intense active minutes; and −157 (−265 to −50) sedentary minutes. Conclusion : Among selected participants treated with TAVR, this study did not provide evidence that a pragmatic home-based mobile health exercise intervention improved daily steps, physical performance or QoL for the overall cohort. However, the intervention did improve several measures of daily activity, particularly among individuals not participating in CR. Trial registry: Clinicaltrials.gov NCT03270124. Abstract : Given the high prevalence and adverse effects of frailty in patients undergoing transcatheter aortic valve replacement (TAVR) and low participation rates in traditional centre-based cardiac rehabilitation (CR), there is a pressing need for alternative strategies to promote post-TAVR rehabilitation. After TAVR, a pragmatic home-based mobile health exercise intervention was successfully implemented and demonstrated high compliance and increased physical activity compared to control, particularly among patients who did not participate in CR. These randomized pilot data could be used to design and power more definitive studies on the optimal implementation and clinical efficacy of this type of intervention. Graphical Abstract: Lay Summary: Given the high prevalence and adverse effects of frailty in patients undergoing transcatheter aortic valve replacement (TAVR) and low participation rates in traditional centre-based cardiac rehabilitation (CR), there is a pressing need for alternative strategies to promote post-TAVR rehabilitation. After TAVR, a pragmatic home-based mobile health exercise intervention was successfully implemented and demonstrated high compliance and increased physical activity compared to control, particularly among patients who did not participate in CR. These randomized pilot data could be used to design and power more definitive studies on the optimal implementation and clinical efficacy of this type of intervention.